Associations between AGT M235T Polymorphism and Cancer: An Updated Meta-Analysis - Kou, Junyan; Huang, Jing (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
We assessed the relationship between AGT gene M235T polymorphism and the susceptibility to cancer by performing an updated meta-analysis. This study retrospectively searched related articles in the electronic databases. Afterwards, we determined combined odds ratios (ORs) and related 95% confidence intervals (CIs) by the fixed- or random-effects model. The present meta-analysis enrolled altogether 9 articles. On the whole, the relationship between AGT M235T polymorphism and the cancer risk was not significant among the entire population (TT vs. MM: OR=1.28, 95%CI=0.80−2.04; TM vs. MM: OR=0.90, 95%CI=0.53−1.52; recessive model: OR=1.13, 95%CI=0.83−1.52; dominant model: OR=0.93, 95%CI=0.55−1.57). Subgroup analysis by ethnicity, cancer type, and study quality for the relationship between the AGT M235T polymorphism and cancer risk showed no significant association. According to findings in the present meta-analysis, AGT M235T polymorphism may not be related to cancer susceptibility.